Pemanfaatan Aset Daerah dalam Menunjang Pelayanan Publik di Kantor Camat Batudaa Pantai Kabupaten Gorontalo - Zulkifli Vebriadi Saleh; Lisda Van Gobel; Yahya Antu (Jurnal Manajemen dan Ilmu Administrasi Publik (JMIAP), 2023)
This study aims to determine the Utilization of Regional Assets in Supporting Public Services at the Batudaa Pantai Sub-District Office, Gorontalo Regency. With sub-focus research namely coordination, maintenance, and supervision. This research uses descriptive qualitative research. The data collection techniques used are: Observation techniques, interviews and recording secondary data. In accordance with the type of research used, the data analysis technique used is qualitative analysis technique. The results showed that, the results of research on the Utilization of Regional Assets in Supporting Public Services seen from the aspects of coordination, maintenance, and supervision are still lacking or not effectively carried out in supporting public services at the Batudaa Pantai Sub-District Office, Gorontalo Regency. The things suggested in this study are the need for the findings of the problems identified in this study such as lack of coordination, lack of asset maintenance, and ineffective supervision can be used as benchmarks or recommendations for improving asset utilization in improving public services.